Non-Invasive Tissue Injury Monitoring Using Bioimpedance Spectroscopy - Aleinik A. N. Aleksandr Nikonorovich; Turgunova N. D. Nataliya Dzhuraboevna; Velikaya V. V.; Musabaeva L. I.; Startseva Z. A.; Mukhamedov M. R. (Radiation Technologies in Medicine, 2015)
Title screen